2015
DOI: 10.1002/jcb.24997
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Rapamycin and Resveratrol Blocks Autophagy and Induces Apoptosis in Breast Cancer Cells

Abstract: Hyperactivation of the mechanistic target of rapamycin complex 1 (mTORC1) is a frequent event in breast cancer and current efforts are aimed at targeting the mTORC1 signaling pathway in combination with other targeted therapies. However, patients often develop drug resistance in part due to activation of the oncogenic Akt signaling and upregulation of autophagy, which protects cancer cells from apoptosis. In the present study we investigated the effects of combination therapy of rapamycin (an allosteric mTORC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 25 publications
3
53
0
1
Order By: Relevance
“…In addition, combination treatment significantly induced apoptosis in cell culture, as measured by the increase in cleavage of apoptotic markers caspase-3 and PARP. Rapamycin and resveratrol also synergized in inhibiting cell motility, in accord with reduced lung colonization in vivo we have previously observed (22).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition, combination treatment significantly induced apoptosis in cell culture, as measured by the increase in cleavage of apoptotic markers caspase-3 and PARP. Rapamycin and resveratrol also synergized in inhibiting cell motility, in accord with reduced lung colonization in vivo we have previously observed (22).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, LAM cells seem to be dependent on even the low levels of autophagy because further inhibition of autophagy induces cell death (21). Our previous studies showed that combination therapy of rapamycin with resveratrol was able to block autophagy and induce apoptosis in TSC2-null cells and in cells with mTORC1 pathway hyperactivation (22,23). In this study, we observed that, in TSC2-null cells, the combination therapy prevented rapamycininduced up-regulation of Akt while maintaining inhibition of S6K1 signaling, indicating that this combination therapy can counter hyperactivation of mTORC1 signaling caused by the loss of TSC2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several compounds have been identified, such as the immunosuppressant and antiproliferative drug rapamycin, such attempts have either led to severe undesired side effects or were not followed up with clinical applications, probably due to toxicity. [23][24][25][26][27][28] Rapamycin, for example, is a potent candidate to trigger autophagic activity in patients diagnosed for different types of cancer. 29,30 However, this compound enhances autophagy by blocking the MTOR (mechanistic target of rapamycin, [serine/threonine kinase]) kinase system, which in turn affects translation.…”
Section: Introductionmentioning
confidence: 99%
“…На наш взгляд, запускать МАФ лучше всего естественным путем, а не используя вещества, ими-тирующие эффект ограничения питания -рапами-цин, ресвератрол и др., так как со временем к ним может развиваться привыкание [30,53]. Именно таким естественным путем это процесс активиру-ется в нашей модели "стационарного клеточного старения".…”
Section: аутофагия клеточное старение и ограничение пролиферацииunclassified